Restrictive immigration policy in Germany: pains and gains foregone? - Gabriel J. Felbermayr; Wido Geis; Wilhelm K. Kohler (Deutsche Bundesbank, 2008)
Many European countries restrict immigration from new EU member countries. The rationale is to avoid adverse wage and employment effects. We quantify these effects for Germany. Following Borjas (2003), we estimate a structural model of labor demand, based on elasticities of substitution between workers with different experience levels and education. We allow for unemployment which we model in a price-wage-setting framework. Simulating a counterfactual scenario without restrictions for migration from new EU members countries, we find moderate negative wage effects, combined with increased unemployment for some types of workers. Wage-setting mitigates wage cuts.
Keywords: J68; J61; J48; 330; wages; migration; Arbeitsnachfrage; Einwanderung; Einwanderungsrecht; Osteuropäer; Lohn; Beschäftigungseffekt; Qualifikation; Deutschland